Utilization of Ferroconcrete and Steel Timber Hybridization Technique in Tall Structure using Analysis tool Etabs : A Review - Rahul Rathore; Lavina Talawale (International Journal of Scientific Research in Civil Engineering, 2021)
As India is a developing nation thus settlement of large population need Multistorey structures. Lateral forces are considered as the forces assigning over a structure in horizontal direction which causes structure instability, deflection and failure. Seismic and wind load is considered as lateral forces. ETABS is an analysis tool which helps in structure modelling and designing as per standard specifications of preferred country. In this paper we are presenting review of researches and publications related to advance technologies in construction design.
Keywords: Hybrid; Composite Structure; Analysis; ETAB; Lateral Forces; Review